(untitled) (Global Journal of Medical Research, 2020)
The Proximate, phytochemicals, elemental and anti-nutrients of annona reticulata seed collected from Michika were investigated. The Proximate, phytochemicals, and anti-nutrients were determined using standard methods, while the elemental composition was determined using Atomic absorption spectrophotometer (AAS) and flame photometer. The result of the proximate analysis shows the presence of Moisture (15.20± 0.02%), crude fibre (32.00 ± 0.01%), crude fat (30.34 ± 0.04 %), ash content (4.5 ± 0.00%), protein (17.12 ± 0.01%) and carbohydrate (37.91± 0.05 %) in the seed. The result of the mineral composition showed Ca (14.40 ± 0.03 mg/ 100 g), Fe (0.32 ± 0.01 mg / 100g), P (46.26 ± 0.02mg /100g), Zn (0.85 ± 0.01mg / 100 g), Na (17.34 ± 0.02mg /100 g), Mg (18.18 ± 0.03mg /100 g) Se (0.12 ± 0.00 mg /100g) were present in the annona reticulate seed.